Football Passing and Control Skills Exercise Model Based on Small Side Games For Ages 12-14 Years - Akhmad Anwar; Widiastuti Widiastuti; Yasep Setiakarnawijaya (BIRCU, 2019)
This study aims to produce soccer passing and control skills training models based on small side games for ages 12-14 years and to test the effectiveness of the models produced. The research method used in this study is the research and development method of Borg and Gall by using 10 stages and with the research subjects are football athletes aged 12-14 years in the East Jakarta football school. This research begins with needs analysis, planning, making trial products, revisions and final products. Test the effectiveness of the model using the loughborough soccer test (LSPT) which is used to determine the level of passing and control abilities of the athlete before and after the treatment model developed. The results of the study show that the product model of this exercise is feasible to use, in the results of small group trials and large groups can explain that the model as a whole can be done well. In the results of the effectiveness test, test the significance of differences with SPSS 16 Independent Samples Test obtained results in the experimental group with an average of 47.61 and the control group with an average of 49.80, these results derived from the test scores in the form of the final time velocity, so the time is smaller the better it gets. Fill in the results of the experimental group and the control group or mean difference = 2.188, t-count = 3.845, df = 58, with ¬-value = 0.000 <0.05, it can be concluded that there are significant differences between the experimental group and the control group. These results indicate that the treatment given to the experimental group, namely the passing and control soccer skills training model based on small side games for 12-14 year olds has higher effectiveness and can improve passing and control skills for athletes aged 12-14 years.